Aspectos do cristianismo no texto dramático Hamlet de William Shakespeare - Cordeiro, João Roberto Marques (2018)
The present work aims to identify and to deepen the most significant elements about Christianity present in William Shakespeare’s Hamlet. Absolutely pacified is the recognition of the presence of such elements, but it remains the discussion of which religion they refer to, Catholicism or Protestantism, as well as the essential nature of the work, if it is Christian or secular. In addition, the reflections and innovations brought by Hamlet will be studied, inasmuch as this is in avant-garde while bringing the conception of the individuality of being. Thus, it will be seen that Hamlet is at the intersection of the metamorphosis between the old and the new, past and future, Medieval and Modern, Catholicism and Protestantism. In view of the evident influence of the historical-social-cultural context in which Shakespeare was inserted, precisely in this work, the present research will deal with the scene in England at the time of its writing, as well as the events that resulted in that situation.